Representation of Environmental Damage in The Novel Pukat and Eliana By Tere Liye - Meilani, Meilani; Supratno, Haris; Setiawan, Setiawan (International Journal for Educational and Vocational Studies, 2020)
Based on the problems in the novel Pukat and Eliana by Tere Liye, it is necessary to do an analysis that discusses the representation of environmental damage in literary works using ecocritical studies. The selection of studies on the representation of environmental damage in literary works as a focus of research has the following reasons: (1) the reflective representation in the novel Pukat and Eliana by Tere Liye is a real-life description of the problems of the characters in the novel with nature and the surrounding environment. The setting used in the story is the forest in Sumatra; (2) the next ecological problem is intentional representation which is a description of the factors that cause damage to the environment in Sumatra; (3) the constructional representation contained in Tere Liye's Pukat and Eliana novel is an impact that occurs as a result of human activity itself. In research with the object of these two novels using qualitative research. This qualitative research as a research step that produces descriptive data in the form of written words of the object being analyzed. The approach in this analysis is an eco-critic approach because this analysis can be used for research on the representation of environmental damage in literary works. Data collection techniques are basically gathering facts related to research problems. Based on research data sources in the form of texts namely novels titled Trawl and novels titled Eliana by Tere Liye the collection of data of this study uses the techniques of listening and documentation study techniques. Ecocriticism studies the ways in which we describe the relationship between humans and their environment. Ecocriticism is also influenced by modern environmental movements. Greg Garrard explored the development of the modern environmental movement and studied several concepts related to eco-criticism, including: (a) pollution, (b) wilderness, (c) apocalypse, (d) housing/dwelling, (e) animals, and (f) earth. Literature itself grows from the environment of society and the natural environment (ecology), which has a function as a medium of representation, views/reflections on the reality of literature which has an important role in changing social values, shared life values and values of local wisdom.